The effect of mouthrinses against oral microorganisms Ação dos enxaguatórios bucais contra microrganismos bucais - José Roberto Cortelli; Raul Emilio de La Sotta Thénoux (Sociedade Brasileira de Pesquisa Odontológica, 2007)
This paper reviews the benefits of the use of antimicrobial mouthrinses for controlling dental biofilm. It is currently known that the human oral cavity is inhabited by approximately 600 to 700 different species of microorganisms, including bacteria, fungi and viruses, organized in biofilms. Biofilm accumulation represents the principal etiologic agent of oral diseases including caries and periodontal diseases. For that reason, prevention of biofilm accumulation has been shown to be associated with the control of diseases. Patient motivation and oral hygiene instruction are claimed to be a major factor influencing the degree of biofilm control. Therefore, mechanical home-care methods, including toothbrushing and flossing, represent the best way for patients to remove biofilm. For many patients, however, the elimination of all biofilm present in the oral cavity through home-care methods could be tedious and time-consuming. Additionally, some local conditions, including malpositioned teeth, presence of bridge-work or orthodontic appliances, among others, may render the mechanical control of biofilm especially difficult. Chemotherapeutic agents, including mouthrinses, could have a key role as adjuncts to daily home care, preventing and controlling supragingival plaque, gingivitis and oral malodor. Indeed, according to the ADA, the active ingredients of mouthwashes must demonstrate a therapeutic effect in vivo and in vitro to be classified as drugs. Several studies included in the present review have demonstrated the effectiveness of mouthrinses containing active ingredients such as chlorhexidine and essential oils in preventing and controlling both supragingival plaque and gingivitis, especially when used adjunctively to regular toothbrushing and flossing procedures. O propósito desta revisão foi mostrar os benefícios decorrentes do uso de enxaguatórios bucais no controle do biofilme dental. Atualmente sabe-se que a cavidade bucal dos humanos é habitada por aproximadamente de 600 a 700 espécies microbianas incluindo bactérias, fungos e vírus. Este aglomerado microbiano, atualmente definido como biofilme dental, é o principal agente etiológico das patologias bucais, incluindo cárie e doença periodontal. Logo, cuidados em relação ao controle destas doenças passam necessariamente pela eliminação ou redução do biofilme dental, incluindo métodos mecânicos adequados de higiene bucal e motivação do paciente. Todavia, a escovação dental e o uso de fio dental podem ser uma tarefa tediosa e consumir tempo exagerado para a rotina de muitos pacientes. Além disso, o controle mecânico do biofilme dental pode ser dificultado por fatores locais como uso de próteses e aparelhos ortodônticos, mau posicionamento dental, entre outros. Assim, o uso de enxaguatórios bucais, associado ao controle mecânico, pode ser incorporado rotineiramente aos cuidados de higiene bucal controlando terapêutica e preventivamente o biofilme supragengival, a gengivite e a halitose. De acordo com a ADA, agentes ativos vinculados aos enxaguatórios bucais devem demonstrar efeitos terapêuticos in vivo e in vitro para que estes sejam classificados como droga. Diferentes estudos incluídos nesta revisão demonstraram que a clorexidina e os óleos essenciais podem, em associação ao hábito regular de escovar os dentes e usar corretamente o fio dental, prevenir e controlar tanto o biofilme supragengival quanto as gengivites.